Optimization of Shrinkage Porosity in AlSi5Cu1Mg Alloy using Response Surface Methodology. Issue 1 (December 2020) - Jaganathan, S; Santhosh, S; Sakthivel, P
Abstract: Zero defects are the ultimate aim of any manufacturer casting aluminium alloys. shrinkage porosity is the major defect in casting AlSi5Cu1Mg alloy using Gravity Die Casting (GDC) process. This paper deals with development of effective approach to describe the optimal condition to reduce the shrinkage porosity formation. Solidification time, metal temperature, and preheat molten temperature are varied using Response Surface Methodology (RSM) based Box-Behnken Design (BBD)and conducted experiments. Solidification time and pouring metal temperature are directly proportional and solidification time and preheat temperature of the mould are indirectly proportional. Theoretical approach is validated with the experimental approach and the predicted values from RSM based BBD is useful and effective in determining the optimized process conditions in GDC process.